Understanding the effects of SMS marketing on consumers' attitude and purchase decision: An Empirical study on Bangladesh - Nayma, Jannatul; Ratul, Salim Shadman; Rahman, Sadia Binte (International Journal of Financial, Accounting, and Management, 2023)
Purpose: Telecom firms and businesses use short message marketing to convey information, advertise their products, and establish customer relationships. This study attempts to understand the effects of SMS marketing on consumer attitudes and purchase decisions from a Bangladeshi perspective. This study extends the Ducoffe model of advertising value (entertainment, informativeness, and irritation) by including two constructs: credibility and personalization. Research methodology: A total of 220 mobile phone users were surveyed using non-probability convenience sampling techniques and data were collected across Dhaka City, Bangladesh. The research model was analyzed using structural equation modeling (SEM). The PLS-SEM (Smart PLS 3.3.9) software was used for path modeling. Before conducting the SEM, this study performed a series of tests to assess the reliability and validity of the data. Results: The findings revealed that informativeness and credibility are the most decisive factors influencing consumer attitudes and purchasing decisions. Limitations: This study neglects privacy concerns, social impact, effort anticipation, and monetary incentives that are crucial to customer attitudes and SMS marketing purchase decisions. This study was conducted using data from a single city in Dhaka, Bangladesh, indicating that the findings are limited to that country's scenario. Contribution: The results of this research provide theoretical contributions to the existing research in this field of study and practical implications for marketing professionals, mobile operators, and third-party service providers in developing appropriate strategies and policies for SMS marketing.